2021
DOI: 10.1016/j.jagp.2020.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Strategies to Promote Social Connections Among Older Adults During “Social Distancing” Restrictions

Abstract: Elsevier has created a COVID-19 resource centre with free information in English and Mandarin on the novel coronavirus COVID-19. The COVID-19 resource centre is hosted on Elsevier Connect, the company's public news and information website. Elsevier hereby grants permission to make all its COVID-19-related research that is available on the COVID-19 resource centre-including this research content-immediately available in PubMed Central and other publicly funded repositories, such as the WHO COVID database with r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
122
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(132 citation statements)
references
References 45 publications
(33 reference statements)
5
122
0
5
Order By: Relevance
“…It is a well-recognized risk factor for premature mortality, and poor physical and psychological wellbeing [5][6][7][8]. For example, previous studies have demonstrated that loneliness in older age is associated with reduced quality of life [9], higher rates of adverse health outcomes and higher mortality rates [6]. Moreover, social isolation possesses a premature mortality risk similar to the risk associated with maintaining an unhealthy diet, lack of physical activity and smoking [6].…”
Section: Introductionmentioning
confidence: 99%
“…It is a well-recognized risk factor for premature mortality, and poor physical and psychological wellbeing [5][6][7][8]. For example, previous studies have demonstrated that loneliness in older age is associated with reduced quality of life [9], higher rates of adverse health outcomes and higher mortality rates [6]. Moreover, social isolation possesses a premature mortality risk similar to the risk associated with maintaining an unhealthy diet, lack of physical activity and smoking [6].…”
Section: Introductionmentioning
confidence: 99%
“…Formal and informal organizations and programs with a component of social contact (eg, peer support/companionship programs, Veteran or religious organizations, Meals on Wheels, exercise programs, self-help groups, and senior centers/programs) are important and potentially under-utilized community resources at the point of discharge from SNFs. Van Orden et al 38 also propose the use of “Connections Plans,” similar to Safety Plans for suicide risk and based on cognitive behavioral strategies, to address social isolation and loneliness in older adults. Engagement of family members and community service providers in creating and sustaining Connection Plans may be a unique, integrated approach to care planning and transitional care in SNFs that could address cognitive barriers to social participation, while furthering recovery goals.…”
Section: Discussionmentioning
confidence: 99%
“…Because of their being at a higher risk of negative outcomes from COVID-19, older adults may self-restrict their activities and interactions even beyond the general population. 16 This, in turn, appears to trigger a range of impact including increasing isolation and loneliness, disrupting daily routines and activities, changed access to essential services such as doctor's visits. The impact can also include some positive changes such as adopting newer technologies, renewed focus on enhancing relationships, and identifying resilience.…”
Section: Dealing With Consequences Of Social Distancing and Lockdownsmentioning
confidence: 99%
“…Two recent reports demonstrate how these approaches can be translated to virtual care and how clinicians may implement strategies to mitigate isolation worsened in the context of social distancing measures. 16,17 It is likely that this specific issue will receive greater attention as we better understand its longer-term consequences. Koenig 18 discusses how of religion and spirituality can play a role as a risk or protective factor.…”
Section: Dealing With Consequences Of Social Distancing and Lockdownsmentioning
confidence: 99%